1997
DOI: 10.1177/001698629704100406
|View full text |Cite
|
Sign up to set email alerts
|

Gifted Women and Marriage

Abstract: This study analyzed the perceived relationship between marriage and achievement among 167 able women, ages 45-65, who were alumnae at the University of Michigan. Women who perceived their husbands as supportive believed they had high potential for achievement, in part, because of the husband's support, the couple's commitment to joint family goals, and willingness to share domestic chores. Women who perceived their husbands as occasionally supportive, felt free to achieve occasionally. These women reported tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 19 publications
2
10
0
2
Order By: Relevance
“…During early adulthood, a gifted adult's career contributes most heavily to life satisfaction (Wirthwein & Rost, 2011b) and most gifted adults across the studies examined here are satisfied with their careers (Perrone, Tschopp, et al, 2010;Siekańska & Sękowski, 2006), but as gifted adults age, contributors to life satisfaction include romantic relationships (Perrone et al, 2006;Perrone-McGovern et al, 2011) and parenting (Ferriman et al, 2009). Strong romantic relationships are even viewed as helpful in attaining professional goals during early and middle adulthood (Hansen & Hall, 1997). By late adulthood (60s and on), romantic relationships and social relationships with friends and family contribute the most to life satisfaction, while intellectual and career pursuits provide less life satisfaction over time (Holahan & Velasquez, 2011;Sears, 1977).…”
Section: Discussionmentioning
confidence: 93%
“…During early adulthood, a gifted adult's career contributes most heavily to life satisfaction (Wirthwein & Rost, 2011b) and most gifted adults across the studies examined here are satisfied with their careers (Perrone, Tschopp, et al, 2010;Siekańska & Sękowski, 2006), but as gifted adults age, contributors to life satisfaction include romantic relationships (Perrone et al, 2006;Perrone-McGovern et al, 2011) and parenting (Ferriman et al, 2009). Strong romantic relationships are even viewed as helpful in attaining professional goals during early and middle adulthood (Hansen & Hall, 1997). By late adulthood (60s and on), romantic relationships and social relationships with friends and family contribute the most to life satisfaction, while intellectual and career pursuits provide less life satisfaction over time (Holahan & Velasquez, 2011;Sears, 1977).…”
Section: Discussionmentioning
confidence: 93%
“…The majority of participants reported that increasing commitment in a romantic relationship resulted in increased life satisfaction and stable and successful long-term marriages and relationships. Previous researchers have documented an association between supportive romantic relationships and life satisfaction in the gifted population (Hansen & Hall, 1997; Sears, 1977). Hansen and Hall (1997) found that married gifted women whose husbands were supportive and collaborative perceived themselves as having high potential for achievement.…”
Section: Discussionmentioning
confidence: 99%
“…Previous researchers have documented an association between supportive romantic relationships and life satisfaction in the gifted population (Hansen & Hall, 1997; Sears, 1977). Hansen and Hall (1997) found that married gifted women whose husbands were supportive and collaborative perceived themselves as having high potential for achievement. The married gifted women in supportive relationships in Hansen and Hall’s study reported positive aspects of their marriages, including good communication, trust, shared goals, emotional intimacy, and increased motivation for excellence in personal and professional goals.…”
Section: Discussionmentioning
confidence: 99%
“…Women gifted in math and science continue to not pursue careers in these fields (Rosser, 2000). A relationship in which women will not have to choose between emotional intimacy and professional achievement, but in which the two are intertwined, is shown to be the best choice for high-achieving females (Hansen & Hall, 1997). Those women who choose a career in science rarely produce as much creative work in the form of research publications as do their male colleagues (Ajzenberg-Selove, 1994;Piirto, 1991).…”
Section: Researching Gifted Women In Sciencementioning
confidence: 99%